2004
DOI: 10.1002/poc.741
|View full text |Cite
|
Sign up to set email alerts
|

Racemization and hydrolysis of (S)‐naproxen 2,2,2‐trifluoroethyl ester in non‐polar solvents by strong neutral bases: implication for ion‐pair kinetic basicity and hydrolysis

Abstract: By using strong neutral bases as catalyst, a detailed investigation of the racemization of (S)‐naproxen 2,2,2‐trifluoroethyl ester was conducted in the non‐polar solvents isooctane, cyclohexane and n‐hexane. The second‐order interconversion constant $k^*_{\rm int}$ as representing the ion‐pair kinetic basicity in isooctane was first estimated and correlated with the equilibrium ion‐pair basicity pKip in tetrahydrofuran, giving slopes of 0.768 and 0.689 for non‐phosphazene and phosphazene bases, respectively, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
2
1
0
Order By: Relevance
“…In addition, a hydrolysis reaction also takes place in the presence of water and strong base, competing over the racemization reaction. 7 This result is in agreement with the investigation carried out by Chavez-Flores and co-worker, where in situ racemization was not observed in the presence of an aqueous buffer solution. 4 From Table 1, it can be observed that the racemization progresses slowly in both isooctane and isooctane−water media with interconversion rate, k int of less than 0.001 h −1 .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, a hydrolysis reaction also takes place in the presence of water and strong base, competing over the racemization reaction. 7 This result is in agreement with the investigation carried out by Chavez-Flores and co-worker, where in situ racemization was not observed in the presence of an aqueous buffer solution. 4 From Table 1, it can be observed that the racemization progresses slowly in both isooctane and isooctane−water media with interconversion rate, k int of less than 0.001 h −1 .…”
Section: Resultssupporting
confidence: 92%
“…In the case of isooctane–water medium, the OH – ion could easily dissociate in the aqueous phase; however, a poor racemization rate of the ( R )-ibuprofen ester was still observed. In addition, a hydrolysis reaction also takes place in the presence of water and strong base, competing over the racemization reaction . This result is in agreement with the investigation carried out by Chavez-Flores and co-worker, where in situ racemization was not observed in the presence of an aqueous buffer solution …”
Section: Resultssupporting
confidence: 91%
“…In comparison with k int = 0.362 h −1 for α‐chlorophenyl acetate at 35 °C, smaller interconversion constants 1.28 × 10 −2 h −1 for the racemization of ( R )‐2,2,2‐trifluoroethyl α‐phenylpropionic thioester and 7.47 × 10 −5 h −1 for that of ( R )‐2,2,2‐trifluoroethyl naproxen ester in isooctane containing ( B ) = 100 mmol dm −3 at 45 °C have been reported 19, 20. This implies that the electron‐withdrawing strength of α‐chloro moiety is much higher than that of 2,2,2‐trifluorothioethyl, 2,2,2‐trifluoroethyl or α‐methyl group in affecting rate‐limiting α‐proton abstraction to form a planar enolate for racemization.…”
Section: Resultsmentioning
confidence: 99%